2022
DOI: 10.1136/bmjopen-2022-066763
|View full text |Cite
|
Sign up to set email alerts
|

What is the prevalence of COVID-19 detection by PCR among deceased individuals in Lusaka, Zambia? A postmortem surveillance study

Abstract: ObjectivesTo determine the prevalence of COVID-19 postmortem setting in Lusaka, Zambia.DesignA systematic, postmortem prevalence study.SettingA busy, inner-city morgue in Lusaka.ParticipantsWe sampled a random subset of all decedents who transited the University Teaching Hospital morgue. We sampled the posterior nasopharynx of decedents using quantitative PCR. Prevalence was weighted to account for age-specific enrolment strategies.InterventionsNot applicable—this was an observational study.Primary outcomesPre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Our initial investigations have shown that CMRs from the WHO and The Economist are moderately correlated with reported COVID-19 deaths while there is no correlation for CMRs produced from IHME estimates. Since under-reporting of COVID-19 deaths is a common problem in countries with low GHS scores, with postmortem surveillance studies in Africa indicating that deaths are undercounted by a factor of 10,90 91 the potential greater reliance on reported COVID-19 deaths by WHO and The Economist may partially explain the different estimates in countries with low GHS scores. Besides varying reliance on reported deaths, all three modelling groups also use different sets of covariates to produce estimates in locations without data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial investigations have shown that CMRs from the WHO and The Economist are moderately correlated with reported COVID-19 deaths while there is no correlation for CMRs produced from IHME estimates. Since under-reporting of COVID-19 deaths is a common problem in countries with low GHS scores, with postmortem surveillance studies in Africa indicating that deaths are undercounted by a factor of 10,90 91 the potential greater reliance on reported COVID-19 deaths by WHO and The Economist may partially explain the different estimates in countries with low GHS scores. Besides varying reliance on reported deaths, all three modelling groups also use different sets of covariates to produce estimates in locations without data.…”
Section: Discussionmentioning
confidence: 99%
“…In the interim, countries may consider improving their surveillance by employing survey methods such as postmortem surveillance studies. One such surveillance study in Zambia found that actual COVID-19 deaths are 10 times greater than reported deaths 90. These methods may assist in constructing more robust measures of COVID-19 impact and therefore assist future studies in providing more robust evaluations of the contributions of pandemic preparedness capacities.…”
Section: Discussionmentioning
confidence: 99%
“…At least one study consecutively tested all decedents brought to a university hospital morgue in Lusaka, Zambia, without regard to symptoms of COVID-19 and found a positivity rate of 15.9% from June to September 2020 12 and 32.0% from January to June 2021. 13 In this setting, unlike in San Francisco, COVID-19 testing before death was rare in the community. Most data on COVID-19 positivity among decedents originate from cases investigated for the cause of death with a high index of suspicion for COVID-19 due to symptoms or death in an area of high COVID-19 morbidity and mortality.…”
Section: Discussionmentioning
confidence: 95%
“…However, testing was prioritized for populations with high COVID-19 mortality, such as older persons, persons dying in nursing facilities, adults in aggregate living, and racial/ethnic groups experiencing COVID-19 disparities. At least one study consecutively tested all decedents brought to a university hospital morgue in Lusaka, Zambia, without regard to symptoms of COVID-19 and found a positivity rate of 15.9% from June to September 2020 12 and 32.0% from January to June 2021 13 . In this setting, unlike in San Francisco, COVID-19 testing before death was rare in the community.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the post-public health emergency phase of the pandemic, testing rates have dwindled down to less than 10 tests/100K/day and 100 tests/100K/day on average for LMICs and HICs respectively (as of September 2023). 9 Low testing rates severely underestimate COVID-19 cases, 10 which not only complicate antiviral demand forecasts but also create additional barriers to the effective distribution and use of antivirals.…”
Section: Introductionmentioning
confidence: 99%